Analisis Implementasi Dan Keberlanjutan Bisnis Kokoro Dango di Kota Palembang - Kheryn Patricia; Leohadi Kurniwan (MDP Student Conference, 2026)
Kokoro Dango is a culinary business that adapts traditional Japanese food, dango, with a modern and local approach. This study aims to analyze the business feasibility, marketing strategy, and potential sustainability of Kokoro Dango based on the final business report. The method used is a qualitative descriptive method with analysis of financial, operational, and marketing report data. The analysis results indicate that Kokoro Dango has good market opportunities, supported by product innovation, digital marketing strategies, and relatively efficient cost management. However, challenges lie in product consistency and increasing brand awareness.